Risques liés aux écoulements torrentiels et leur gestion à Chosica (Lima, Pérou) - Alexis Ricardo Mejía Uquiche; Josyane Ronchail (EchoGéo)
Chosica city (capital of Lurigancho-Chosica district, in Lima city in Peru), because of its physical characteristics, is affected frequently by torrential flows. These events are not only related to heavy rainfalls (usually when the El Niño phenomenon happens), but also because of the geomorphologic conditions of the torrents, which are colonized in their low and central parts, producing human losses and economic damages. We analyze the hazard (the intensity and frequency of torrential flows), the fragility of housing, the degree of exposure to the hazard, and the level of risk management during the last three events of 2012, 2015 and 2017. The installation of flexible barriers in 2016 appears to have contributed to damage reduction in 2017, when rains were heavier than in previous years.